2012
DOI: 10.1080/00087114.2012.678091
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characteristics of callus cells of Nicotiana tabacum L. var. BELW3 grown in presence of NaCl

Abstract: An investigation by electron microscopy has been carried out on Nicotiana tabacum L. var. BELW3 callus cells grown in a medium containing different NaCl concentrations (0.1, 0.2, 0.3 M) for 60 days to study the salt effect at cell level. Control N. tabacum callus exhibited parenchymatous cell types with normal cytoplasm, nucleus, organelles and membranes, together to cells forming meristematic zones by normal mitosis and cytokinesis. The callus cells exposed to the lowest salt dose did not show specific struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…In our study, short term transfers are responsible for the disorganization of the chloroplasts, testified by the loss of their internal membrane organization. Similar responses under stress conditions have been reported for terrestrial plants, such as in cotton cells under cadmium treatment (Daud et al, 2009), cucumber and soybean cold-treated cells (Lee et al, 2002;Glinska et al, 2009), and N. tabacum callus cells under salt stress (Bennici et al, 2012). The disorganization of chloroplasts in meristematic cells (especially after 3 weeks at pH 6.8) found in the present study could be explained by the translocation of photosynthates from aboveground to belowground tissues, which has been shown to decrease the leaf chlorophyll content of Thalassia hemprichii under elevated CO 2 conditions (Jiang et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…In our study, short term transfers are responsible for the disorganization of the chloroplasts, testified by the loss of their internal membrane organization. Similar responses under stress conditions have been reported for terrestrial plants, such as in cotton cells under cadmium treatment (Daud et al, 2009), cucumber and soybean cold-treated cells (Lee et al, 2002;Glinska et al, 2009), and N. tabacum callus cells under salt stress (Bennici et al, 2012). The disorganization of chloroplasts in meristematic cells (especially after 3 weeks at pH 6.8) found in the present study could be explained by the translocation of photosynthates from aboveground to belowground tissues, which has been shown to decrease the leaf chlorophyll content of Thalassia hemprichii under elevated CO 2 conditions (Jiang et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…It was speculated that starch synthesis plays a role in lessening the hyperosmotic stress as osmoticum. A total disorganization of the protoplast in callus cells was reported in other plants, possibly caused by dehydration (Bennici and Tani, 2012 ). Disintegration of chloroplasts and mesophyll cells end the photosynthesis, thus, maintaining structural integrity is necessary in plant growth (Bennici and Tani, 2012 ).…”
Section: Discussionmentioning
confidence: 64%
“…In addition, ultrastructural changes at the cellular level in a salt-adapted potato callus lines grown in 150 mM NaCl (Queirós et al, 2011 ) demonstrated that salt-adapted potato cell line contained more large starch, reduced membrane system and no vesicles. Although the ultrastructural alterations induced by saline have been reported in many plant cells (Yamane et al, 2004 ; Miyake et al, 2006 ; Ferreira and Lima-Costa, 2008 ; Bennici and Tani, 2009 , 2012 ), information regarding the effects of salinity on potato cells cultured in vitro is not specified and is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…This fact confirmed the possibility of generating a plant from callus under dolomite treatment. It seems like Bacinni and Tani [35] study on Nicotiana tabacum L. callus.…”
Section: Plos Onementioning
confidence: 81%